Nutrition, hydration and supplementation considerations for mountaineers in high-altitude conditions: a narrative review - Karpęcka-Gałka, Ewa; Frączek, Barbara (Frontiers in Sports and Active Living, 2024)
Staying and climbing in high mountains (>2,500 m) involves changes in diet due to poor access to fresh food, lack of appetite, food poisoning, environmental conditions and physiological changes. The purpose of this review is to summarize the current knowledge on the principles of nutrition, hydration and supplementation in high-altitude conditions and to propose practical recommendations/solutions based on scientific literature data. Databases such as Pubmed, Scopus, ScienceDirect and Google Scholar were searched to find studies published from 2000 to 2023 considering articles that were randomized, double-blind, placebo-controlled trials, narrative review articles, systematic reviews and meta-analyses. The manuscript provides recommendations for energy supply, dietary macronutrients and micronutrients, hydration, as well as supplementation recommendations and practical tips for mountaineers. In view of the difficulties of being in high mountains and practicing alpine climbing, as described in the review, it is important to increase athletes’ awareness of nutrition and supplementation in order to improve well-being, physical performance and increase the chance of achieving a mountain goal, and to provide the appropriate dietary care necessary to educate mountaineers and personalize recommendations to the needs of the individual.